Physalis angulata Leaf Ethanol Extract Reduces Oxidative Stress and Improves Endothelial Progenitor Cells in L-NAME-Induced Hypertensive Rats - Dian Nugrahenny; Nur Permatasari; Setyawati Soeharto; Indriati Dwi Rahayu; Edwin Widodo; Karyono Mintaroem; Hidayat Sujuti; Retty Ratnawati; Elly Mayangsari; Dicky Faizal Irnandi; Lavina Sofia Ardani; Tika Ardhini Wardoyo; Nathania Bella Claresta; Nura Fattah Cantika Yoga; Adinda Chika Anindita; Niarti Ulan Sari Siarnu; Fardizia Putri Alia (HAYATI Journal of Biosciences, 2023)
This study aimed to evaluate the effects of ciplukan (Physalis angulata L.) leaf ethanol extract on L-NG-nitroarginine methyl ester (L-NAME)-induced hypertensive rats. We randomly divided twenty-five Wistar rats into five groups. The sham group was given a PBS injection. The hypertensive group was injected with L-NAME on days 1 to 28. Three groups of hypertensive rats were given the extract on days 4 to 28. Blood pressure was measured using the tail-cuff method on days 0, 4, 10, and 27. The endothelial progenitor cells (EPCs) in the blood were measured by flow cytometry as a percentage of circulating angiogenic cells (CACs, CD34+/CD309+/CD45+) and endothelial colony-forming cells (ECFCs, CD34+/CD309+/CD45-). Serum NO and MDA levels, as well as serum SOD activity, were measured colorimetrically. Serum TNF-α levels were measured by the ELISA method. The ciplukan leaf extract reduced systolic and diastolic blood pressure, reduced the percentage of EPCs in the blood, increased serum NO levels, reduced MDA levels, increased serum SOD activity, and reduced serum TNF-α levels in L-NAME-induced hypertensive rats. It is concluded that ciplukan ethanol leaf extract exerts protective effects on L-NAME-induced hypertensive rats. These study results can strengthen the scientific basis of using ciplukan leaf ethanol extract to treat hypertension.